Implementasi Hill Cipher Pada Kode Telepon dan Five Modulus Method dalam Mengamankan Pesan - Patmawati Hasan; Selviana Yunita; Dony Ariyus (STMIK PONTIANAK, 2020)
The development of sophisticated technology in this era is increasingly rapid, messages that are hidden or kept a secret from people who want to access the secret message need to be safeguarded by the security of the message. One way to be able to hide the secret message so that it is not known or understood by people who do not have rights in the message is to change the message into a secret password and insert using cryptographic and steganographic techniques. A security system built using a combination of the Hill cipher algorithm and Five Modulus Method with the aim of making security strong and layered without reducing or damaging the text messages in the image. The system built using the programming language Matlab. The algorithm used has advantages in encrypting data. Hill Cipher uses a size (m x m) matrix as the key to encrypting and decrypting data. Whereas for steganography uses the Five Modulus Method by checking all pixels in blocks (k x k) and converting each pixel into a number that is divisible by 5. The results of this study are security systems that use the Combination of Hill Cipher and Five Modulus Methods in Securing Text Messages. Based on the results of the accuracy of testing five (5) times on different plaintexts, an accuracy rate of 100% is found, ie there is no difference in the results of encryption or decryption.